'It's not that easy to solve': edTPA and preservice teacher learning. Issue 2 (3rd April 2018) - Paugh, Patricia; Wendell, Kristen Bethke; Power, Christine; Gilbert, Michael
Abstract: This three year qualitative study of a university pilot of the edTPA, a performance assessment for preservice teachers, questioned candidates' learning at the nexus of claims that the edTPA serves a dual role as both a formative assessment for candidates' ongoing learning as well as a summative assessment of their readiness to teach. The analysis highlighted affordances and constraints of the assessment in the areas of: (1) depth of professional learning, (2) differentiation for diverse learners, (3) focus on school, community and family context, (4) professional reflection within classroom realities, and (5) as an evaluation tool. The discussion positions the findings alongside other published implementation studies of the edTPA in terms of current reforms. It especially problematizes the positioning of preservice teachers as professional learners in light of pressures for compliance and standardization.